Scambi e commerci in area Vesuviana : i dati delle anfore dai saggi stratigrafici i.e. (impianto elettrico) 1980-81 nel Foro di Pompei - Bernal Casasola, Darío,; Cottica, Daniela, (Roman and late antique Mediterranean pottery ;, 2019)
Transport amphorae are one of the best archaeological indicators for evaluating the economy and trade of societies in the ancient world. This monograph, produced by researchers from the University of Cadiz and the Ca' Foscari University of Venice, includes the study of nearly five hundred of these commercial containers, recovered during the pioneering stratigraphic excavations carried out in 1980-1981 at the Forum of Pompeii, called conventionally 'Impianto Elettrico'. The work represents the first Pompeian monograph dedicated exclusively to the analysis of the amphoric evidence brought to light by archaeological excavation activities in the city buried by the eruption of Vesuvius and analyses in diachronic perspective the main productions in circulation between the VI/V BC and the year 79 AD.